Quantitative Study of the Factors That Influence the Incidence of Low Birth Weight - Retno Dewi Prisusanti; Achmad Jaelani Rusdi; Rahma Putri Kasimbara; Suwito Suwito; Dewi Anggraeni (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Background: Adolescents undergo changes where In Indonesia, the incidence of LBW is still relatively high, this is evidenced by the presence of data which shows that the birth rate of babies with normal weight is still below the expected rate. The global prevalence of LBW is 15.5%. A total of around 20 million LBW are born every year and 95.5% of them come from developing countries. The infant mortality rate (IMR) in Indonesia increased in 2012 from 19 per 1,000 live births to 22.23% per 1,000 live births (SUPAS, 2015). Based on the results of the East Java National Socio- Economic Survey (Susenas) 2011–2013, the infant mortality rate (IMR) in East Java in 2013 was 27.23% per 1,000 live births (East Java Province Health Profile, 2014). Purpose: This study aims to determine the factors that influence the incidence of low birth weight babies. Method: This type of research is analytic observational. With the analytical design of the case study study (case study) and using a retrospective approach. The sample used in this study was an accidental sample of all babies born at Bangil Hospital, Pasuruan Regency with birth weight less than 2,500 grams, as many as 34 babies. Result: From the results of research conducted at Bangil Hospital, Pasuruan Regency, the results of the factors that influence the occurrence of low birth weight in Bangil Hospital, Pasuruan Regency, namely, the nutritional factors of pregnant women with a result of 58.8%, Parity of a mother who experiences pregnancy> 4 times tends to experiencing low birth weight with a percentage of 29.4%, followed by maternal age as much as 14.7%. Conclusion: It is expected that pregnant women with high risk factors for pregnancy in the categories of pregnant women <20 years, parity of pregnant women> 4x, and nutritional status (LILA <23.5cm) can reduce the incidence of low birth weight at Bangil Hospital, Pasuruan Regency.